Antibacteria Activity Peel and Seed Extracts of Rambutan (Nephelium lappaceum L.) Against MDR Bacteria Causing Urinary Tract Infections - Mukaromah, Ana Hidayati; Cahyaningrum, Dea Galuh; Putri, Desty Ratna; Jannah, Erni M; Rinaldi, Muhamad Rizqi; Wardoyo, Fandhi Adi; Ariyadi, Tulus; Hikmah, Annisa Nurul; Darmawati, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
Multidrug-resistant (MDR) - Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumoniae) are the main causes and have become serious problems in urinary tract infections, so antibacterial agents derived from biological materials are needed. ESBL-E. coli and ESBL-K. pneumoniae bacteria are resistant to extracts from rambutan peels and seeds, but there is no knowledge of the use of different solvents, such as n-hexane, chloroform, or ethanol. The objective of this research was to assess the antibacterial activity of rambutan peels and seed extracts (n-hexane, chloroform, and ethanol) against MDR bacteria that cause urinary tract infections (UTI). The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) values for antibacterial activity were calculated using agar well diffusion and dilution procedures. The results demonstrated that the ethanol extract of rambutan peels had inhibitory zones against MDR K. pneumoniae and E. coli that varied from 9.00 to 14.13 mm. 15.625 mg/mL For MDR E. coli and 3.90 mg/mL for MDR K. pneumoniae, respectively, the MIC value was determined. The MBC value was 62.50 mg/mL for MDR K. pneumoniae and 31.25 mg/mL for MDR E. coli. Conclusion: Of the six rambutan peel and seed extracts, the ethanol extract has greater potential as an antibacterial agent. It is advised that more in-vivo studies be done to understand how the antibacterial activity operates.The benefits of research for the science are providing alternative solutions to antibiotic resistance, to further advancing the field of antimicrobial research, and reducing the risk of bacterial infections.